2015
DOI: 10.1007/s00128-015-1581-x
|View full text |Cite
|
Sign up to set email alerts
|

Residues of Polychlorinated Biphenyls (PCBs) in Sediment from CauBay River and Their Impacts on Agricultural Soil, Human Health Risk in KieuKy Area, Vietnam

Abstract: An evaluation of the PCB residues from CauBay River and KieuKy area, Vietnam was carried out. CauBay River has been playing an important role in irrigated water supply for agriculture activities at KieuKy area in the downstream. The PCBs concentrations of sediment, soil samples were analyzed and obtained results indicated the wide extent of contamination of PCBs in CauBay River (from 30.74 to 167.35 ng g(-1) dry weight) and KieuKy area (from 21.62 to 60.22 ng g(-1) dry weight). This clearly reflected the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 7 publications
0
2
1
Order By: Relevance
“…Whereas, the comparison of the mean PCBs concentration in sediments of Post-monsoon with other studies showed that the ∑PCBs concentration of this study was significantly lower than those reported from Makelele, Kalamu, and Nsanga, Congo (Kilunga et al 2017); River Ravi, Pakistan (Baqar et al 2017); Liaohe River, China (Lv et al 2020); CauBay River, Vietnam (Toan and Quy 2015); Sarno River, Italy (Montuori et al 2014); Soan River, Pakistan (Malik et al 2014); and River Chenab, Pakistan (Eqani et al 2012). However, the ∑PCBs concentration was slightly lower or somewhat comparable to those studies recorded from River Thames, England (Lu et al 2017); Yamuna River, India (Kumar et al 2013); Songhua River, China (Cui et al 2016) and Bahlui River, Romania (Neamtu et al 2009).…”
Section: Comparison With Previous Studies Worldwidecontrasting
confidence: 85%
“…Whereas, the comparison of the mean PCBs concentration in sediments of Post-monsoon with other studies showed that the ∑PCBs concentration of this study was significantly lower than those reported from Makelele, Kalamu, and Nsanga, Congo (Kilunga et al 2017); River Ravi, Pakistan (Baqar et al 2017); Liaohe River, China (Lv et al 2020); CauBay River, Vietnam (Toan and Quy 2015); Sarno River, Italy (Montuori et al 2014); Soan River, Pakistan (Malik et al 2014); and River Chenab, Pakistan (Eqani et al 2012). However, the ∑PCBs concentration was slightly lower or somewhat comparable to those studies recorded from River Thames, England (Lu et al 2017); Yamuna River, India (Kumar et al 2013); Songhua River, China (Cui et al 2016) and Bahlui River, Romania (Neamtu et al 2009).…”
Section: Comparison With Previous Studies Worldwidecontrasting
confidence: 85%
“…Thus simply banning manufacture is in insufficient to reduce exposure 4 . PCBs can threaten human health via their potential carcinogenic effects 5 . Adverse health effects such as neurological effects, in humans exposed to PCBs have been investigated in laboratory and epidemiological studies 6 .…”
mentioning
confidence: 99%
“…Until 2015, sediment levels of PCBs decreased compared to 31.72-167.32 ng/g [5]. Toan et al reported that the main source of contamination in Hanoi city could originate from the dielectric oil used in old hanging transformers and capacitors [6].…”
Section: Introductionmentioning
confidence: 99%